2008
DOI: 10.1080/07347330802359578
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Optimism–Pessimism and Health-Related Quality of Life in Breast Cancer Survivors

Abstract: Few studies have investigated the influence of optimism-pessimism in breast cancer survivors. This study used a retrospective design with 268 adult women who completed the Minnesota Multiphasic Personality Inventory (MMPI) as part of their medical care approximately 10 years prior to their breast cancer diagnosis and Medical Outcome Study Short-Form General Health Survey (SF-36 or SF-12), on average, 8 years after diagnosis. MMPI pessimism scores were divided into quartiles, and t tests were used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 34 publications
7
40
0
1
Order By: Relevance
“…These explanatory or attributional styles have been linked to health-related issues, including depression and illness (Fresco, Alloy, & Reilly-Harrington, 2006;Peterson et al, 2008). The Attributional Style Questionnaire (ASQ) was used to examine the degree to which respondents attributed life events to internal, Downloaded by [National Pingtung University of Science and Technology] at 01:36 06 February 2015 stable, and global causes (i.e., optimistic) as opposed to external, unstable, and specific (i.e., pessimistic) causes (Peterson et al, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…These explanatory or attributional styles have been linked to health-related issues, including depression and illness (Fresco, Alloy, & Reilly-Harrington, 2006;Peterson et al, 2008). The Attributional Style Questionnaire (ASQ) was used to examine the degree to which respondents attributed life events to internal, Downloaded by [National Pingtung University of Science and Technology] at 01:36 06 February 2015 stable, and global causes (i.e., optimistic) as opposed to external, unstable, and specific (i.e., pessimistic) causes (Peterson et al, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…The SF-36 and the SF-8 have been widely used in cancer health-related QOL studies and have been shown to have high reliability and validity when utilized in cancer populations. [6871]…”
Section: Methodsmentioning
confidence: 99%
“…In such cases where people choose and endure an unpleasant experience, individuals may subsequently reconcile themselves by exaggerating the resulting benefits (a phenomenon termed "cognitive dissonance reduction") 18 . After a course of noxious chemotherapy for breast cancer, for example, some women may be unduly confident about having conquered cancer [19][20][21] . Whereas a degree of optimism may be productive, an exaggerated false sense of security could theoretically jeopardize subsequent patient outcomes by contributing to lapses in follow-up appointments, gaps in long-term medication adherence, or denial over a possible recurrence [22][23][24] .…”
Section: Cognitive Dissonance Reductionmentioning
confidence: 99%